One step solvothermal synthesis of Bi/BiPO4/Bi2WO6 heterostructure with oxygen vacancies for enhanced photocatalytic performance. Issue 6 (15th April 2018) - Yang, Fan; Zhu, Ximiao; Fang, Jianzhang; Chen, Dongdong; Feng, Weihua; Fang, Zhanqiang
Abstract: In this work, a plasmonic metallic Bi deposited BiPO4 /BiWO6 heterostructure with surface oxygen vacancies was synthesized through one-step solvothermal method. The successful synthesis of material was confirmed by a series of characterization techniques such as X-ray diffraction, X-ray photoelectron spectroscopy, UV–vis diffuse reflection spectroscopy, electron paramagnetic resonance, transmission electron microscope, photoluminescence spectroscopy. The characterization results showed that the surface oxygen vacancies were concentrated on the surface of BiPO4 . The photocatalytic activity of Bi/BiPO4 /Bi2 WO6 was evaluated by photocatalytic decomposition of methylene blue and 2, 4-Dichlorophenol under simulated sunlight irradiation. Meanwhile, with the addition of hydrogen peroxide, the photocatalytic efficiency would be further improved. The presence of rich surface oxygen vacancies and photo-induced electron were beneficial to produce hydroxyl radicals. The enhanced photocatalytic activity of Bi/BiPO4 /Bi2 WO6 heterostructure was ascribed to high separation efficiency of photo-generated electron–hole pairs, which aroused by the synergistic effects of heterojunction among different components, surface plasmonic resonance effect of Bi, and the surface oxygen vacancies.